The Application Problem-Based Learning Based E-module to Increase The Ability of Logical Thinking And Decrease Students’ Misconception of Class X 3 of SMAN Kebakkramat in The Year 2014/2015 - Memorita Walasari; Puguh Karyanto; Dewi Puspita Sari; Purwi Hartiti (Universitas Sebelas Maret, 2015)
The aim of this research were to increase the ability of logical thinking and decrease students’ misconception in SMAN Kebakkramat throught applying Problem-Based Learning based e-Module. This research is classroom action research that consist of two cycles. Every cycle consists of four phases, they are planning, action, observation, and reflection. The subject of the research was students of class X3 of SMAN Kebakkramat. They are 16 boys and 26 girls. Validity of data uses data triangulation technique. Collecting data techniques are test, observation, and interview. This research was descriptive qualitative. The result shows that students’ misconception decrease. The percentage of misconception in each cycles are 65,57% at pre cycle, 53,63% at first cycle, and 27,47% at second cycle (all aspects of ecology concepts). Those concepts are attribute aspect in population, attribute in community, food chain and food webs, SETS (Science, Environment, Technology, and Society) aspect in ecology context. The percentage of logical thinking ability in each cycles are 37,27% at pre cycle, 51,26% at first cycle, and 60,25% at second cycle (in all aspects: generalisation aspect, analogy aspect, causal relation aspect, hypotetic silogisme, categorial silogisme, alternative silogisme and entimem). The conclusion of this research was application of Problem-Based Learning based on e-Module increased the ability of logical thinking and decreased student’s misconceptions.Keywords: Problem Based Learning based E-Module, misconception, and logical thinking skill